Suppose -4*u + 450 = u. Suppose -69 = -4*n + 3*x, -5*n + 3*x = -2*x - u. Solve p - n = -4*p for p.
3
Let x be (9 - 9)*3⁄6. Solve x = d + 3*d for d.
0
Let p be 2 - ((-6)/(-2))/(-3). Solve p*w + 2 = -10 for w.
-4
Let z be (24 - 2) + 19⁄19. Solve -z = -4*u - 7 for u.
4
Let p(h) = h**2 - 5*h - 6. Let w be p(6). Let f be w/(11-2). Let c(x) = -x + 7. Let l be c(3). Solve f = l*i - 8 - 0 for i.
2
Let n(k) = -7 + k + 1 + 2. Let g be n(6). Let b = 3 + -3. Solve g = -2*s - b for s.
-1
Let b(j) = j2 - 2*j - 2. Let d be b(4). Let q(f) = -2*f2 + 2*f + 3. Let l be q(-2). Let h be (-6)/4*30/l. Solve 0 = -h*i - 21 + d for i.
-3
Suppose -5*d + 104 = 29. Solve -u - 4*u = d for u.
-3
Let n = 47 - 44. Solve 5 = -2*q - n for q.
-4
Let i(g) = g**2 - 4*g - 20. Let a be i(9). Suppose -q + 0*q = -25. Let t be 22⁄10 - 5/q. Solve -3*z = t*z - a for z.
5